2011
DOI: 10.1177/1742715011416886
|View full text |Cite
|
Sign up to set email alerts
|

Organizational democracy, ethics and leadership: The mediating role of organizational politics

Abstract: There has been a growing concern amongst commentators about the disconnection between the apparent pluralisation of society and the relatively limited adoption of democratic practices in the corporate workplace. This paper examines the experience of employees in an international broking company in order to explore the extent to which a political leadership perspective can provide insight into furthering organizational democratisation. Attention is given to the integral relationship between democracy, ethics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
(73 reference statements)
0
5
0
2
Order By: Relevance
“…Instead, they run using the command and control model (Fenton, 2011). In spite of considerable improvements capable of promoting organizational democracy, however, dominates the enactment of organizational hierarchy (Clarke, 2011). In the media, at schools and work we constantly hear that we live in a democratic world.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they run using the command and control model (Fenton, 2011). In spite of considerable improvements capable of promoting organizational democracy, however, dominates the enactment of organizational hierarchy (Clarke, 2011). In the media, at schools and work we constantly hear that we live in a democratic world.…”
Section: Introductionmentioning
confidence: 99%
“…It further found that an ethical workplace always promotes a sense of belongingness and an imperative bond between the employees and their leadership, which in return positively affects the underlying level of commitment among employees. Similarly, another study conducted by Clarke, (2011) found that organizational politics is an important determinant of workplace ethics, which in turn has an indirect implication on the commitment level of employees towards their organizations. The study further evaluated that positive implication of organizational politics on workplace ethics can be achieved through close supervision and controlled communication among employees.…”
Section: Employee's Commitmentmentioning
confidence: 85%
“…More specifically, they stated that organizational democracy needs organizational politics and organizational politics needs organizational democracy. Similarly, in another study, it was found that organizational policy has an important role in structuring organizational democracy (Clarke, 2011). In these studies, constructive political behaviors and the effects of these behaviors on organizational democracy were discussed.…”
Section: Introductionmentioning
confidence: 93%